Electron affinity of tricyclic, bicyclic, and monocyclic compounds containing cyanoenones correlates with their potency as inducers of a cytoprotective enzyme. Issue 17 (1st September 2016) - Bensasson, René V.; Dinkova-Kostova, Albena T.; Zheng, Suqing; Saito, Akira; Li, Wei; Zoete, Vincent; Honda, Tadashi
Graphical abstract: Abstract: Tricyclic, bicyclic, and monocyclic compounds containing cyanoenones induce various anti-inflammatory and cytoprotective enzymes through activation of the Keap1/Nrf2/ARE (antioxidant response element) pathway. The potency of these compounds as Nrf2 activators was determined using a prototypic cytoprotective enzyme NAD(P)H:quinone oxidoreductase 1 (NQO1) in Hepa1c1c7 murine hepatoma cells. The electron affinity (EA) of the compounds, expressed as the energy of their lowest unoccupied molecular orbital [E (LUMO)], was evaluated using two types of quantum mechanical calculations: the semiempirical (AM1) and the density functional theory (DFT) methods. We observed striking linear correlations [ r  = 0.897 (AM1) and 0.936 (DFT)] between NQO1 inducer potency of these compounds and their E (LUMO) regardless of the molecule size. Importantly and interestingly, this finding demonstrates that the EA is the essentially important factor that determines the reactivity of the cyanoenones with Keap1.